1999
DOI: 10.1016/s0895-7061(98)00229-5
|View full text |Cite
|
Sign up to set email alerts
|

Fosinopril decreases levels of soluble vascular cell adhesion molecule-1 in borderline hypertensive type II diabetic patients with microalbuminuria

Abstract: Angiotensin converting enzyme inhibitors (ACE-I)are a mainstay for the treatment of heart failure, and of diabetic microalbuminuria. Recently ACE-I have been found to decrease plasma levels of circulating vascular cell adhesion molecule-1 (cVCAM-1) in patients with congestive heart failure. As increased cVCAM-1 levels are pathognomonic for diabetics with microangiopathy, we investigated the effects of ACE-I on plasma levels of cVCAM-1, intercellular adhesion molecule (cICAM-1), and cE-selectin in microalbuminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 48 publications
4
24
0
1
Order By: Relevance
“…The plasma levels of all of the target parameters did not differ significantly between hypertensive patients after ACE inhibitor treatment and the control group of healthy individuals. Failure to demonstrate significant decrease of E-selectin and ICAM-1 levels with ACE inhibitor therapy is in agreement with a previous study performed by Gasic et al 23 in borderline hypertensive patients with diabetes. On the contrary, Ferri et al 7 observed a significant 30-80% decrease of E-selectin and ICAM-1 levels in hypertensive patients treated with ACE inhibitors.…”
Section: Discussionsupporting
confidence: 92%
“…The plasma levels of all of the target parameters did not differ significantly between hypertensive patients after ACE inhibitor treatment and the control group of healthy individuals. Failure to demonstrate significant decrease of E-selectin and ICAM-1 levels with ACE inhibitor therapy is in agreement with a previous study performed by Gasic et al 23 in borderline hypertensive patients with diabetes. On the contrary, Ferri et al 7 observed a significant 30-80% decrease of E-selectin and ICAM-1 levels in hypertensive patients treated with ACE inhibitors.…”
Section: Discussionsupporting
confidence: 92%
“…Gasic S et al (1999) [224] In microalbuminuric patients with NIDDM serum levels of cVCAM-1 decreased by -19%. Plasma levels of cE-selectin, cICAM-1, PAI-1 and TPA were unaffected.…”
Section: Fosinoprilmentioning
confidence: 99%
“…Analysing data provided by Gasic et al, [224] the ACEi fosinopril (10 mg/day) administered over 12 weeks to 11 microalbuminuric patients with non-insulin-dependent diabetes mellitus (NIDDM) provided the following actions: serum levels of cVCAM-1 decreased by -19% (CI: -25% to -13%) after treatment with fosinopril (P = .003) and were no longer different from those of the control group. In contrast, plasma levels of E-selectin, ICAM-1, plasminogen activator inhibitor (PAI-1) and tissue plasminogen activator (TPA) were unaffected.…”
Section: Part IV -Anti-inflammatory Effects Of Ace-imentioning
confidence: 99%
“…ACEIs possess pharmacological properties, which could delay the development of atherosclerosis and increase plaque stability. 5,6,49,50 In addition, ACEIs may shift the fibrinolytic balance from coagulation to lysis by reducing the angiotensin II-dependent production and secretion of plasminogen activator inhibitor-1. 5,6 Results of our overview support the hypothesis that for the same degree of BP lowering, ACEIs might be superior to CCBs in the protection against incident or recurrent CHD.…”
Section: Ancillary Properties Of Aceis and Ccbsmentioning
confidence: 99%